Perfect Fools: Sanctity, Madness, and the Theory of Ambiguous Performance - Madigan, Todd (Religions, 2025)
The theory of cultural pragmatics describes the process through which social actors guide their symbolic performances. However, this theory has not paid sufficient attention to the audience’s role in constructing the meaning of these performances. Instead of positing that the intended meanings performed by actors are internal states to be either correctly or incorrectly perceived by an audience, my contention is that the purported intentions of actors are in fact audience constructions that are ascribed to actors. I support this claim through the development of what I call ambiguous performances. These are performances that combine elements of incompatible social roles. This combination creates a multistable performance, one that allows for one of several mutually exclusive interpretations. Because of this, ambiguous performances compel each audience member to choose between multiple conflicting interpretations, and in order to choose an interpretation, audience members must look beyond the performance to aspects of their own identity. I illustrate this process through an analysis of holy fools, historical figures who have appeared periodically throughout Christendom over the course of many centuries. These individuals were sometimes canonized as saints, but more often simply considered insane, an interpretive dichotomy that reveals the ambiguous nature of their performances.